2016
DOI: 10.21010/ajid.v11i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Flock-Based Surveillance for Low Pathogenic Avian Influenza Virus in Commercial Breeders and Layers, Southwest Nigeria

Abstract: Background: Flock surveillance systems for avian influenza (AI) virus play a critical role in countries where vaccination is not practiced so as to establish the epidemiological characteristics of AI needed for the development of prevention and control strategies in such countries. Materials and Methods: As part of routine AI monitoring in southwest Nigeria, a competitive ELISA was used for detecting influenza A virus antibodies in the sera of 461 commercial breeder and layer birds obtained from different floc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…However, current evidence reveals that they could potentially play a significant role in the future emergence of the influenza pandemic, either directly as a H9 AIV subtype virus or as a result of the donation of internal genes to HPAI pandemic subtypes (Peacock et al, 2019b). The finding in this study is similar to that reported by Oluwayelu et al (2017), who detected H9 influenza virus antibodies in commercial breeders and layers birds in South western Nigerian States.…”
Section: Discussionsupporting
confidence: 86%
“…However, current evidence reveals that they could potentially play a significant role in the future emergence of the influenza pandemic, either directly as a H9 AIV subtype virus or as a result of the donation of internal genes to HPAI pandemic subtypes (Peacock et al, 2019b). The finding in this study is similar to that reported by Oluwayelu et al (2017), who detected H9 influenza virus antibodies in commercial breeders and layers birds in South western Nigerian States.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, there are a pair of studies showing high seropositivity against H9N2 in Nigerian poultry and agricultural workers, however, no virus has been isolated from this country [57,58]. Although surveillance for HPAIVs is ongoing in Nigeria, it is unclear whether protocols are used that would pick up the presence (or absence) of H9N2 viruses, therefore it remains unclear whether the virus is/was present in this region.…”
Section: History and Phylogeography Of H9n2 Virus In Poultrymentioning
confidence: 99%
“…Recently, one isolate of an H9 related to the Korean subclade A h9.2.2.2 was reported in poultry from North Korea (Zhang et al 2017b). Additional studies suggest serological evidence of H9N2 IAVs in poultry in Romania, Nigeria, Laos, and Thailand, but lineage characterization is lacking (Sonnberg et al 2012;Oluwayelu et al 2017;Coman et al 2018;Karlsson et al 2019).…”
Section: Eurasian Lineagementioning
confidence: 99%